2013
DOI: 10.1371/journal.pone.0065787
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Risk Factors in North West Tanzania: The Effect of Spraying, Nets and Wealth

Abstract: Malaria prevalence remains high in many African countries despite massive scaling-up of insecticide treated nets (ITN) and indoor residual spraying (IRS). This paper evaluates the protective effect of pyrethroid IRS and ITNs in relation to risk factors for malaria based on a study conducted in North-West Tanzania, where IRS has been conducted since 2007 and universal coverage of ITNs has been carried out recently. In 2011 community-based cross-sectional surveys were conducted in the two main malaria transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
43
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 40 publications
13
43
3
Order By: Relevance
“…Since parasite density is controlled by acquired immunity in the infected host 7 adults are more likely than children to carry sub-microscopic infections. 29,30 Our study showed a higher prevalence of sub-microscopic infections among older children and adults (>5years) than among children <5years (10.3% versus 3.4%) which is expected. On the other hand, prevalence by microscopy was highest among children <5 years (10.3%), an indication of higher parasite densities among the children who are still in the process of building up their protective immunity.…”
Section: Discussionsupporting
confidence: 54%
“…Since parasite density is controlled by acquired immunity in the infected host 7 adults are more likely than children to carry sub-microscopic infections. 29,30 Our study showed a higher prevalence of sub-microscopic infections among older children and adults (>5years) than among children <5years (10.3% versus 3.4%) which is expected. On the other hand, prevalence by microscopy was highest among children <5 years (10.3%), an indication of higher parasite densities among the children who are still in the process of building up their protective immunity.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies examining the effect of ITN use on infection prevalence have relied on microscopy to measure P. falciparum prevalence [10, 13, 3033], however 47% of all infections detected in these surveys were sub-microscopic and SAC were more likely to have sub-microscopic infections than younger children [14]. Unlike microscopy, rtPCR can detect prevalent low-density asymptomatic infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognised that people with low SES are usually prone to vector-borne diseases [29][30][31][32] including Dengue, although not in all cases as shown by a recent systematic review of the link between Dengue and Socioeconomic status [33]. Our study described the group that is more at risk than others and the spatial distribution of Dengue virus cases has been produced.…”
Section: Discussionmentioning
confidence: 81%